Exploring the role of unconventional T cells in rheumatoid arthritis - Xu, Tangqing; Cai, Hao; Liu, Jianye; Mao, Xingxing; Chen, Yulong; Chen, Minhao; Wang, Youhua (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disorder characterized by sustained synovial inflammation and the gradual destruction of joint structures. Although conventional T cells have historically been viewed as central to RA pathogenesis, increasing attention has recently focused on unconventional T cell subsets, such as natural killer T (NKT) cells, mucosal-associated invariant T (MAIT) cells, and gamma delta T (γδ T) cells. Functioning as a bridge between innate and adaptive immunity, these cells contribute to RA immunopathogenesis by producing cytokines, exerting cytotoxic effects, and interacting with various immune and stromal cells. This review offers a comprehensive analysis of the immunological characteristics and pathogenic roles of unconventional T cell subsets in RA. NKT, MAIT, and γδ T cells contribute to the amplification of inflammatory responses and joint tissue destruction through diverse mechanisms, exhibiting unique tissue tropism and functional plasticity. Recently, novel therapeutic strategies have been developed to target these subsets, including modulation of antigen presentation pathways, inhibition of pro-inflammatory signaling cascades, and reprogramming of cellular functionalities. Advancements in single-cell omics and spatial immune profiling have facilitated the precise identification and characterization of pathogenic unconventional T cell subsets in the RA synovium, thereby paving the way for personalized immunotherapeutic approaches.